Collateral damage. (Economist, 1996)
In the battle between Microsoft and Netscape for the web browser market, Sun Microsystems flinches every time that Netscape is dealt a blow by Microsoft. Together, Netscape and Sun have generated great enthusiasm for Sun's new programming language, Java, which could challenge Microsoft's overall dominance of the software industry. Netscape has promoted the idea that its web browser and Java together could replace Microsoft's Windows operating system as the primary way that individuals and software interact with their PC. The writer discusses why Sun is not directly threatened by the prospect of a Microsoft victory and Sun's development of software for cheap and simple consumer devices, from mobile telephones to television set-top boxes, that are linked to the Internet.